2009
DOI: 10.1088/0960-1317/19/2/025005
|View full text |Cite
|
Sign up to set email alerts
|

Machining with micro-size single crystalline diamond tools fabricated by a focused ion beam

Abstract: A study was carried out to understand the physics of micro-scale mechanical machining (henceforth referred to as ‘micro-machining’) with a micro-size tool using a five-axis ultra-precision machine. A micro-size single crystalline diamond (SCD) tool with sharp cutting edges fabricated by a focused ion beam (FIB) was employed to orthogonal-machine four materials (three polycrystalline metals with various grain sizes and one amorphous metal plating material). Since the wealth of knowledge of macro-machining canno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The material properties, such as the crystallographic orientation [138,148,174], grain size [175], grain boundary [147,176,177], or hard particles [178][179][180] of or in workpiece material, have important effects on the cutting process. Therefore, in this section, the influence of the material properties would be discussed in three aspects: the influence of ductile materials, the influence of brittle materials and the influence of the defects, such as grain size, grain boundary and hard particle, on the micro/nanocutting process.…”
Section: Influence Of Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The material properties, such as the crystallographic orientation [138,148,174], grain size [175], grain boundary [147,176,177], or hard particles [178][179][180] of or in workpiece material, have important effects on the cutting process. Therefore, in this section, the influence of the material properties would be discussed in three aspects: the influence of ductile materials, the influence of brittle materials and the influence of the defects, such as grain size, grain boundary and hard particle, on the micro/nanocutting process.…”
Section: Influence Of Materials Propertiesmentioning
confidence: 99%
“…Hard particle in workpiece also plays an important role in plastic deformation and surface generation during cutting process. Ding et al [179] found the formation of voids on the machined surface caused by the hard particles in Al RSA-905 and Al-6061. When the top layer of the machined surface is removed, the hard particle could be found near the voids.…”
Section: Influence Of Grain Size Grain Boundary and Hard Particlementioning
confidence: 99%
“…It has been reported that changes in cutting forces, chip formation and surface finish occur when machining multi-phase or multi-grain materials [9][10][11]. It has also been reported that hard phases or particles present in work material lead to the prevalence of voids and the consequent degradation of the surface finish [12]. This paper examines the extent of this phenomenon and offers an explanation for the causes.…”
Section: Introductionmentioning
confidence: 95%
“…Ge et al [15] conducted ultra-precision turning tests to investigate the surface/subsurface motion of the NP in the metal matrix composites, deeming that the distance from the NP to material free surface determines the NP be pulled out or pressed into the machined surface. The research by Ding et al [16] suggests that NPs play an important role in the void generation of the machined workpiece. Xu et al [17] found that the NP could be removed as a whole entity or be fractured into several pieces because of the strong interaction between the NP and the cutting tool, and the fractured NP pieces could enlarge the void regions on the machined surface.…”
mentioning
confidence: 99%